Toxicity of selected insecticides on Epilachna indica (Coleoptera: Coccinellidae: Epilachninae) - Zakaria, Mohd Ibnur Syawal (2017)
Epilachna indica (Coleoptera: Coccinellidae: Epilachninae) is a twelve spotted lady bird beetle and a serious pest of vegetables. The phytophagous ladybird beetle attacks various vegetable families such as Solanaceae, Cucurbitaceae and Fabaceae. A study was conducted to evaluate the toxicity of selected insecticides against the larvae of Epilachna indica. Very few information is available on the toxicity of commonly use insecticides in vegetables against this insect. The types of conventional insecticide used in this research were deltamethrin, cypermethrin, spinosad and fipronil. The bioassays was conducted using the leaf of Luffa acutangula dipped in difference concentrations of insecticide (100 ppm, 50 ppm, 25 ppm, and control) and exposed on the insect. The minimum of five replicates was used and mortality was recorded after 24, 48 and 72 hours. The data was analyzed using probit and ANOVA with means separation by Tukey. The most toxic insecticide identified and the order of toxicity was deltamethrin more toxic than cypermethrin, spinosad and fipronil. The LC50 of deltamethrin and cypermethrin after 72 hours was 5.53 ppm and 6.45 ppm respectively.